ART ECOSYSTEM OF THE HGATERI TRADITIONAL MUSIC GROUP IN JAYAPURA PAPUA - Kaiway, Yudhi Aji Ristanto; Mudra, I Wayan; Sariada, I Ketut (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
This study looks at the world of traditional Papuan music, focusing on the Hgateri group. Hgateri is a traditional music group in Jayapura that keeps Wonti-Waropen music alive and is a symbol of efforts to preserve traditional music in Papua. This research aims to describe the traditional Papuan music ecosystem by studying the Hgateri group. Using a qualitative method, we gathered data through observations, interviews with the group leader, and documents. The results show that Hgateri has found new ways to introduce traditional music to young people. This study looks at how this group works in different areas: culture and society, where Hgateri helps keep their culture alive and brings the Wonti people closer together; economics, where the group has shown that traditional arts can make a steady income; education, where Hgateri helps young people grow and learn; laws, where the group understands the importance of being legal; and technology, where they combine old and new ways to create exciting performances. This research helps us better understand traditional Papuan music and how to keep it alive.